2018
DOI: 10.1007/s00787-018-1154-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental depressive symptoms as a risk factor for child depressive symptoms; testing the social mediators in internationally adopted children

Abstract: Parental depressive symptoms have shown to be associated with offspring depression but much of the research has been focused on maternal depression. The aim of our study was to investigate the extent to which depressive symptoms of both parents associate with offspring depressive symptoms and whether social factors mediate these associations using data from adopted children with no shared genetic background. Data were derived from the Finnish Adoption survey study (a subsample of adopted children aged between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Paternal depression effects on adopted children have exemplified the non-genetic environmental effects of paternal postpartum depression. For example, depressive symptoms as measured by the Children's Depression Inventory have been greater in a study on Finnish adopted children of depressed fathers including negative mood and interpersonal problems [37].…”
Section: Paternal Depression Effects On Grade School Childrenmentioning
confidence: 99%
“…Paternal depression effects on adopted children have exemplified the non-genetic environmental effects of paternal postpartum depression. For example, depressive symptoms as measured by the Children's Depression Inventory have been greater in a study on Finnish adopted children of depressed fathers including negative mood and interpersonal problems [37].…”
Section: Paternal Depression Effects On Grade School Childrenmentioning
confidence: 99%
“…Parental mental health. The link between adoptive parent mental health and children's behaviour or mental health was explored in seven studies (Colvert, et al, 2008;Gagnon-Oosterwaal, et al, 2012;Goldberg and Smith, 2013;Hails, et al, 2019;Hornfeck, Bovenschen and Heene, 2019;Liskola, et al, 2018;Smith-McKeever, 2004). One measured general parental mental health (Colvert), three focused on parental depression (Goldberg and Smith; Hails; Liskola), five explored parental stress (Gagnon-Oosterwaal;Miller, et al, 2009;Santos-Nunes, et al, 2018;Smith-McKeever;Smith, et al, 2018) and one assessed parent self-regulation (Hornfeck).…”
Section: Parent Factorsmentioning
confidence: 99%
“…Third, studies in this issue of ECAP consider not only maternal but also paternal mental health and behavior as a possible source of risk. While neither paternal alcohol abuse nor body mass index appears to be related to offspring mental health [13,16], other research has shown that paternal depression predicts behavioral and emotional problems [18][19][20], especially in boys [21]. Moreover, paternal parenting style may also be a key risk factor of children's long-term behavioral and emotional difficulties [22].…”
mentioning
confidence: 99%